Differentiating true androgen receptor inhibition from cytotoxicity-mediated reduction of reporter-gene transactivation in-vitro. (December 2017) - Marin-Kuan, Maricel; Fussell, Karma C.; Riederer, Nicolas; Latado, Helia; Serrant, Patrick; Mollergues, Julie; Coulet, Myriam; Schilter, Benoit
Abstract: In vitro effect-based reporter assays are applied as biodetection tools designed to address nuclear receptor mediated-modulation. While such assays detect receptor modulating potential, cell viability needs to be addressed, preferably in the same well. Some assays circumvent this by co-transfecting a second constitutively-expressed marker gene or by multiplexing a cytotoxicity assay. Some assays, such as the CALUX®, lack this feature. The cytotoxic effects of unknown substances can confound in vitro assays, making the interpretation of results difficult and uncertain, particularly when assessing antagonistic activity. It's necessary to determine whether the cause of the reporter signal decrease is an antagonistic effect or a non-specific cytotoxic effect. To remedy this, we assessed the suitability of multiplexing a cell viability assay within the CALUX® transcriptional activation test for anti-androgenicity. Tests of both well-characterized anti-androgens and cytotoxic compounds demonstrated the suitability of this approach for discerning between the molecular mechanisms of action without altering the nuclear receptor assay; though some compounds were both cytotoxic and anti-androgenic. The optimized multiplexed assay was then applied to an uncharacterized set of polycyclic aromatic compounds. These results better characterized the mode of action and the classification of effects. Overall, the multiplexed protocol added value to CALUX test performance. Highlights: Discerning between antagonistic and/or cytotoxic dose-response effect Method enhancement by multiplexing antagonistic assay with cytotoxicity assessment Optimization allowed accurate antiandrogen characterization of unknown substances. Application of multiplexed cytotoxicity is required for endocrine activity screening.